2017
DOI: 10.1002/pssb.201700262
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure High‐Temperature Synthesis of MoS2/Holey Graphene Hybrids and Their Performance in Li‐Ion Batteries

Abstract: Hybrids of holey graphene (HG) and MoS 2 have been prepared by a treatment of few-layered HG and amorphous MoS 3 , taken in a weight ratio of %5 and %10%, at 100 bar and 600 C under vacuum. A study of the products by electron microscopy, X-ray diffraction, Raman scattering, and X-ray photoelectron spectroscopy has detected coating of graphene stacks by thin MoS 2 layers. The near-edge X-ray absorption fine structure spectroscopy has revealed a covalent bonding between MoS 2 and HG components. A hybrid with 5 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
(30 reference statements)
2
7
0
Order By: Relevance
“…The productive discussions during the meeting (which has been held on 19–24 March 2017) were provided by perfect organization and nice natural environment, including ski slopes, at Krasnaya Polyana resort (Sochi, Russia). The contributions (in total an amount of 30) of this Special Issue are covering research work related to production, characterization and application of the nanocarbon materials which include diamonds, carbon nanotubes, graphene other types of nanocarbon materials, and their composites . Traditionally for the NPO Workshop series there is also some portion of reports devoted to non‐carbon materials demonstrating properties and phenomena analogous to those observed for nanocarbons.…”
supporting
confidence: 89%
“…The productive discussions during the meeting (which has been held on 19–24 March 2017) were provided by perfect organization and nice natural environment, including ski slopes, at Krasnaya Polyana resort (Sochi, Russia). The contributions (in total an amount of 30) of this Special Issue are covering research work related to production, characterization and application of the nanocarbon materials which include diamonds, carbon nanotubes, graphene other types of nanocarbon materials, and their composites . Traditionally for the NPO Workshop series there is also some portion of reports devoted to non‐carbon materials demonstrating properties and phenomena analogous to those observed for nanocarbons.…”
supporting
confidence: 89%
“…The low temperature was chosen according to the DTG curve, which showed that MoS 3 transforms to MoS 2 between 385 and 450 °C (Figure ). The XRD analysis of 30MoS 2 /HG400a and 30MoS 2 /HG500a (Figure a) detected reflections from the HG planes and the planes of hexagonal MoS 2 . This confirms the crystallization of MoS 2 at the temperatures used.…”
Section: Resultssupporting
confidence: 56%
“…All spectra have two main peaks located at ≈285.5 and ≈292.8 eV and assigned to 1s → π* and 1s → σ* electron transitions, respectively. The peaks appearing between these resonances are usually due to functionalized carbon atoms . They have a negligible intensity in the HG600a spectrum indicating that the treatment conditions lead to the removal of oxygen groups, which were present in the initial HG sample (Figure S5, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the edge carbon atoms, constituting the boundaries of the holes, may work as the sites for anchoring of redox‐active substance on the graphene plane. Hot pressing of such composites improves the bonding between the components that causes decrease of the resistance for charge transport in Li‐ion cells . However, before the development of synthesis procedures for such hybrids, it is necessary to find the limiting values of pressure and temperature, which do not degrade the electrochemical characteristics of the HG component.…”
Section: Introductionmentioning
confidence: 99%